Spatiotemporal evolution and prediction of blue–green–grey-space carbon stocks in Henan Province, China - Zhou, Kai; Wei, Xinyu; Wang, Yanjie; Wang, Jinhui; Wang, Zhifang; Zhang, Yichuan (Frontiers in Environmental Science, 2025)
Changes in blue–green–grey spaces use greatly influenced the carbon-storage capabilities of ecosystems, which is crucial for maintaining the carbon balance of regional ecosystems.By combining the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model with the Patch-generating Land Use Simulation (PLUS) model, this study evaluates the spatiotemporal evolution of blue–green–grey spatial carbon stocks in Henan Province, China, and predicts the relationship between blue–green–grey spatial changes and carbon stocks under four future scenarios. This total amount of carbon stocks decreased by 39.75 × 106 Mg from 2000 to 2020. The pattern of carbon-storage spatial distribution is characterised by ‘higher in the west and lower in the east’. The urbanisation process in Henan Province has been accelerating, and the area of grey space has increased rapidly, resulting in a substantial decline in carbon storage. Grey-space development will be severely constrained under the ecological protection (EP) scenario by 2050, where the grey-space area will decrease by 33.15% compared to that in 2020. Under the cultivated-land protection (CLP) scenario, the growth of the green space will increase considerably and carbon storage will reach the highest level. This paper offers a solid scientific foundation for promoting low-carbon and green development as well as optimising the spatial arrangement of Henan Province, China.